Leishmanicidal activity of the crude extract, fractions and major piperidine alkaloids from the flowers of Senna spectabilis - Albuquerque Melo, Gabriela Muniz de; Rodrigues Silva, Marcela Campelo; Guimaraes, Thais Pereira; Pinheiro, Katia Mantovani; Brito da Matta, Carolina Barbosa; Queiroz, Aline Cavalcanti de; Pivatto, Marcos [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Alexandre-Moreira, Magna Suzana; Viegas, Claudio (Elsevier B.V., 2014)
Senna spectabilis (sin. Cassia excelsa, C. spectabilis) is an endemic tree of South America and Africa, very common in Brazil, where it is known as canafistula-de-besouro and cassia-do-nordeste. In folk medicine, this plant is indicated for the treatment of constipation, insomnia, anxiety, epilepsy, malaria, dysentery and headache. Phytopharmacological studies have also confirmed anticonvulsive, sedative, anti-malarial, antimicrobial and cytotoxic properties of many parts of S. spectabilis. In this communication, we present a comparative study of the leishmanicidal activity of the crude ethanolic extract, its fractions and also the two major alkaloidal metabolites (-)-cassine/(-)-spectaline, trying to establish a relationship between the presence of piperidine alkaloidal constituents and leishmanicidal activity. The growth inhibitory effect of promastigote forms of Leishmania major was determined for the crude extract, fractions of the flowers of S. spectabilis and a mixture of (-)-cassine/(-)-spectaline in comparison to pentamidine used as standard drug. The cytotoxic effects were assessed on macrophage strain J774 by lactate dehydrogenase assay. Fractions dichloromethane (FL-DCM) and n-butanol (FL-Bu) and a mixture of (-)-cassine/(-)-spectaline (similar to 7:3) exhibited significant activity against the parasite Leishmania major (IC50 values of 0.6 +/- 0.1 mu g/ml, 1.6 +/- 0.9 mu g/ml and 24.9 +/- 1.4 mu g/ml, respectively), without toxic effects on murine macrophages. Due to the promising results elicited, further studies in vivo need to be performed to confirm the therapeutic potential of Senna spectabilis. (C) 2013 Elsevier GmbH. All rights reserved.
Keywords: Antiprotozoal activity; Leishmanicidal activity; Senna spectabilis; Cassia spectabilis; Piperidine alkaloids